(3YbO GdLhgQ GdKejf aj CQHYjf MOjKG ef CMGOjK SjO GdeQSdjfs - (3GdLqQGMj GdYLdhfj GdOeTbqj, CHh GdaOGA, ESeGYjd Hf eMeO Hf YHO GdgGOj, (B1162 (3g`s ((3YHO GdbGOQ GdNGdOj GdJejej GdfGHdSjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj QaY ebOGQ Cgd GdMOjK bO hbaJ Ydi QSGdI CXfgG dYV Gdecjjf dcfj de Cba Ydi GSeg hdG Ydi JSejJgG hgj eTJedI Ydi CMGOjK ef ChGFd HYV cJH GdMOjK efgG GdcJH GdSJI GdeTghQI hbO PcQ ajgG s
(3BNQgG (B:s
(3hefgG eG PcQg SjOfG hTjNfG hHQcJfG GdeQMhef GdTjN Ydj bOS Gddg QhMg HSfOg Edi SjOfG YHO Gddg Hf YeQh Hf GdYGU hYHO Gddg Hf YHGS QVj Gddg Yfge bGdG cGf QShd Gddg Udi Gddg Ydjg hSde jOYh HgPg GdOYhGJ hjNJe HgG hgPG BNQ eG COQJ LeYgs
(3JHUQI GdYfhGf (B:s
(3de JTQ GdeUGOQ (B- (3GdJj hbaJ YdjgG (B-(3dfSHI gPG GdcJGH ddYLdhfj QZe hLhO YOI fSN eNWhWI dg hQZe WHGYJg (B( (3eMeO hGFd GdMfHdj (B- (3OGQ GdHTGFQ (B) (3hdcf GdefShd ddYLdhfj gh (B( (3YbO GrdnLrhngQ GdKejf HTQM GdnMpOjK GdeSdSd HGdOeTbjjf(B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\325 (3g`s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdMOjK hGdeUWdMs